2019
DOI: 10.1186/s13059-019-1881-2
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas13d mediates robust RNA virus interference in plants

Abstract: Background: CRISPR-Cas systems endow bacterial and archaeal species with adaptive immunity mechanisms to fend off invading phages and foreign genetic elements. CRISPR-Cas9 has been harnessed to confer virus interference against DNA viruses in eukaryotes, including plants. In addition, CRISPR-Cas13 systems have been used to target RNA viruses and the transcriptome in mammalian and plant cells. Recently, CRISPR-Cas13a has been shown to confer modest interference against RNA viruses. Here, we characterized a set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
157
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(162 citation statements)
references
References 61 publications
(92 reference statements)
4
157
1
Order By: Relevance
“…In this study we have shown that Cas13b RNA guides are able to induce the knockdown of target genes in mosquito cells, both through Cas13b-mediated enhancement of suppression and, unexpectedly, through Cas13b-independent, sequence-specific, RNA knockdown. This is in contrast to work describing the use of Cas13b guides in mammalian and plant cells where RNA knockdown was entirely dependent on the presence of Cas13b 12,17 . We hypothesise that the phenomenon is dependent on base-pair complementarity between the guide and the target RNA, leading to recognition and processing of the target RNA by cellular RNA interference (RNAi) systems.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…In this study we have shown that Cas13b RNA guides are able to induce the knockdown of target genes in mosquito cells, both through Cas13b-mediated enhancement of suppression and, unexpectedly, through Cas13b-independent, sequence-specific, RNA knockdown. This is in contrast to work describing the use of Cas13b guides in mammalian and plant cells where RNA knockdown was entirely dependent on the presence of Cas13b 12,17 . We hypothesise that the phenomenon is dependent on base-pair complementarity between the guide and the target RNA, leading to recognition and processing of the target RNA by cellular RNA interference (RNAi) systems.…”
Section: Discussioncontrasting
confidence: 73%
“…The Cas13b-independent effect was detected due to the use of a ZsGreen mock control plasmid (pZsG). Previous work in plant and mammalian cells has not reported interference by the guides alone 12,17 . In plants, the targeting guides were used without Cas13b 17 , while in mammals, the authors used a catalytically inactive dCas13b 12 .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Previously, we have described a set of optimal design rules for RfxCas13d guide RNAs (gRNAs), and developed a computational model to predict gRNA efficacy for all human protein-coding genes 5 . However, there is a growing interest to target other types of transcripts, such as noncoding RNAs (ncRNAs) 6,7 or viral RNAs 8,9 , and to target transcripts in other commonly-used organisms [10][11][12][13] . Here, we predicted relative Cas13-driven knock-down for gRNAs targeting messenger RNAs and ncRNAs in six model organisms (human, mouse, zebrafish, fly, nematode and flowering plants) and four abundant RNA virus families (SARS-CoV-2, HIV-1, H1N1 influenza and MERS).…”
Section: Introductionmentioning
confidence: 99%